Akuntabilitas dalam Perspektif Akuntansi Syariah: Studi Kasus pada Badan Amil Zakat Nasional Kabupaten Kebumen - Novendi Arkham Mubtadi; Gita Paramita Agustin; Dewi Susilowati (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
The purpose of this study is to analyze the accountability between reporting information ZIS (Alms, infaq and sadaqah) institutions revealed Zakat Institution with the concept of Shariah Accounting. This study uses the method of documentation and observation to management ZIS (Alms, infaq and sadaqah) is done based on those in item concept Shariah Accounting by analyzing report on the use ZIS (Alms, infaq and sadaqah) based on three aspects is god, human, and nature. The results of this study indicate that management ZIS (Alms, infaq and sadaqah) in BAZNAS Kebumen there is still deficiencie in conformity with the concept Shariah Accounting aspects of God, human, and nature has been done by BAZNAS Kebumen.Keywords: Accountability, Shariah Accounting, Zakat Institution